‘An analysis of corporate disclosure and potential improvements in disclosure in quoted companies in the automotive industry’. - Dissak Delon, Samuel (2011)
This work is an attempt to assess the effectiveness and impact of disclosure levels in quoted companies in the automotive industry. Changing practices and behaviors is not always the end result desired, but merely a mean to reach the desired end. National and International accounting bodies are aiming to require from firms more disclosure of past and prospective information. The first chapter is exploring some theoretical foundations and empirical studies on disclosure, also looking at the recent changes made with regards to international accounting standards harmonization and financial reporting between countries. In addition, we will define and analyze in depth what desired information is for investors. Betson (1973) argued that perhaps more important is the concept of fairness, the belief that all investors, large and small, insiders and outsiders, should have equal access to relevant information. One need access to accurate information in order to make informed investment decision.